Prevalence and Its Related Factors of Undernutrition among Under 5-Year-Old Children, Fars, Iran 2017-2018 - Seyedeh-Masomeh Derakhshandeh-Rishehri; Azam Farmani; Mina Zarmehrparirouy; Abdolrasool Hemmati; Shiva Faghih; Razieh Shenavar (Journal of Nutrition and Food Security, 2023)
The present study aimed to investigate the prevalence and related factors of under-nutrition among under 5-year-old children in Fars province, Iran.  Methods: This cross-sectional survey was conducted during 2017-2018 in Fars province of Iran. The study consisted of 606 children (0-59 months) from 13 regions of Fars province. A structured questionnaire collected the data, and under-nutrition indices, including stunting, wasting, and underweight, were investigated by the mixed-effects ordinal logistic regression model. Results: The prevalence of stunting, underweight, and wasting were 2%, 4%, and 4.1%, respectively. Low birth weight was a risk factor for three undernutrition indices (P < 0.001; P < 0.001; and P = 0.004). Urban children were significantly more underweight and wasted than rural children (P = 0.001; and P = 0.002, respectively). Under-nutrition rates were impressed by the family size, mother's education, and father's occupation.  Conclusion: The prevalence of undernutrition in children can be reduced by identifying and controlling significant factors, including birth weight, maternal education, type of settlement, family size, and father's occupation.